Muslim Community Awareness of Women's Education and Its Impact on Social Change in North Padang Lawas Indonesia - Anita Khairani Siregar; M. Iqbal Abdul Muin (Assyfa Journal of Islamic Studies, 2026)
This study aims to analyze the collective awareness of Muslim communities toward women’s education and its implications for social change in Pasar Gunung Tua Village, Padang Bolak District, North Padang Lawas Regency. This research is motivated by the existence of community views influenced by patriarchal culture, where men’s education is prioritized over women’s education. In addition, economic factors and social perspectives also influence the continuity of women’s education within the community. This study employs a qualitative method with a case study approach. Data collection techniques were conducted through observation, in-depth interviews, and documentation involving village officials, religious leaders, community leaders, parents, and women who are currently or have previously pursued education. The findings show that public awareness regarding the importance of women’s education has gradually increased. Family support, religious perspectives, and social development are the main factors encouraging this awareness. However, there are still several obstacles, such as economic limitations and traditional cultural views that place women primarily in domestic roles. This study concludes that women’s education has an important contribution in encouraging social change through improving family quality, expanding women’s social participation, and increasing public awareness of the importance of education.